Applied Regression Modelling to Propose Recommendations for the Development of Banking Services: A Case Study of Commercial Banks in Vietnam - Linh, Phan Thi (Bright Publisher, 2024)
The trend of global economic integration has created conditions for the strong development of our country's economy during the integration process. More and more foreign banks have been participating in our country's financial market, creating increasingly fierce competitive pressure in the commercial banking system. Despite many efforts, domestic banks still face difficulties in surviving and developing. Facing so many competitive challenges and the entry of foreign banks requires banks to have a clear strategy to maintain and increase market share. Many banks have made great strides in service quality, improving management levels, and applying applications such as Internet banking, ebank, Fintech, etc. Providing customers, the best quality of service has become more critical than ever if banks want to survive and develop in the current period. Therefore, the article aims to discover the essential factors contributing to developing commercial banking services in Vietnam. In addition, policy implications for banking service development are proposed. Based on the goal, the author surveyed 500 customers using the banking services, applied the multiple linear regression method, and processed data using SPSS 20.0. The key findings showed seven factors affecting banking service development with a significance of 0.05. The contributions of this study have focused on analyzing and identifying factors and the level of influence of factors on banking service development. Based on the research results, the author proposed some recommendations to help commercial bank leaders develop banking services in the coming time. The research novelty discusses the proposed seven policy recommendations, which include (1) tangibles, (2) responsiveness, (3) competence, (4) empathy, (5) reliability, (6) management capacity, and (7) technological capacity. Finally, the results are also scientific evidence and are very important for managers and policymakers for Vietnamese commercial banks to apply to contribute to developing the banking services to the higher demand of customers.